Examining the Role of Religiosity in Moderating Online Purchase Intentions Toward Halal Food: A Study of Muslim Consumers in Indonesia - Laelani Rukmana; Wa’adarrahmah; Dia Purnama Sari (Universitas Islam Negeri Mataram, 2025)
The rapid growth of internet usage in Indonesia, driven by technological advancements, has transform consumer behavior, including the way individuals purchase food products online. In the context of halal food consumption, understanding the factors that influence online purchase intention is increasingly important. This study aims to examine the effects of halal awareness, trust, perceived ease of use, and halal certification on consumers’ intention to purchase halal food through online applications, with religiosity serving as a moderating variable. Grounded in the Technology Acceptance Model (TAM) framework, this study adopts a quantitative approach. Data were collected through a self-administered questionnaire survey involving 260 respondents from several cities in Indonesia and analyzed using Partial Least Square (PLS). The results indicate that trust, perceived ease of use, and halal certification significantly influence consumers’ intention to purchase halal food online, whereas halal awareness does not have a direct effect. Furthermore, religiosity does not strengthen the relationships between halal awareness, trust, perceived ease of use, and halal certification with purchase intention; instead, it weakens these direct relationships. These findings suggest that functional and institutional factors play a more dominant role than individual religiosity in shaping online halal food purchase intentions, offering important implications for platform providers and halal food businesses in designing effective digital marketing strategies.